A specific haplotype in potential miRNAs binding sites of secreted frizzled-related protein 1 (SFRP1) is associated with BMD variation in osteoporosis - Amjadi-Moheb, Fatemeh; Hosseini, Seyed Reza; Kosari-Monfared, Mohadeseh; Ghadami, Elham; Nooreddini, Hajighorban; Akhavan-Niaki, Haleh (Gene, 2018)
Osteoporosis is an important multifactorial disease which is largely influenced by Wnt signaling pathway. Considering regulatory single nucleotide polymorphisms in Wnt signaling pathway may pave the road of understanding the genetic basis of predisposition to osteoporosis. The aim of this study was to determine the possible association between variants of SFRP1 and WNT5b, and osteoporosis incidence risk. The study population comprised 186 osteoporotic patients and 118 normal subjects from Amirkola Health and Ageing Project. rs1127379 (c.1406A>G) and rs3242 (c.3132C>T) variants in 3′UTR of SFRP1 gene, and rs3803164 (c.236C>T) in 3′UTR and rs735890 (c.622-536A>G) in intron 4 of WNT5b gene were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Regression analyses were used to calculate the association of genotype frequencies with bone mineral density (BMD) and bone mineral content (BMC) values of participants. Bioinformatics algorithms were used to detect the effect of each SNP on the secondary structure of mRNA, and predict putative 3′UTR microRNA target sites and splicing sites changes by related SNPs. WNT5b rs735890 was associated with lumbar spine BMD, BMC, and femoral neck BMC (P = 0.035, P = 0.007, and P = 0.038, respectively). WNT5b rs3803164, and SFRP1 rs3242 were significantly associated with lumbar spine BMD (P = 0.028 and P = 0.030, respectively). SFRP1 rs1127379 was associated with lumbar spine BMD in the male gender. Haplotype analysis showed a significant association of SFRP1 c.[1406A; 3132C] haplotype with lumbar spine BMD, and BMC (P = 0.019 and P = 0.030, respectively), and SFRP1 c.[1406G; 3132C] haplotype with lumbar spine BMC (P = 0.045). In silico analyses revealed that the G allele of SFRP1 rs1127379, and WNT5b rs3803164 appear as more possible target sites for many miRNAs. This study is the first evidence of the association of WNT5b rs735890, and c.[1406A; 3132C] and c.[1406G; 3132C] haplotypes of SFRP1 with BMD variation in osteoporosis, probably by altering microRNA target sites, in elderly persons. [Display omitted] •WNT5b rs735890 is associated with lumbar spine BMD, BMC, and femoral neck BMC•WNT5b rs3803164, and SFRP1 rs3242 are significantly associated with lumbar spine BMD•SFRP1 c.[1406A; 3132C] haplotype is significantly associated with lumbar spine BMD, and BMC